Role of Auxin and Microclimate on the Success of Rooted Cuttings of Cocoa - Adi Prawoto; Arifin .; Syamsul Bachri; K.C Setyaningtyas (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2007)
In Indonesia, cocoa reproduction by cuttings is undeveloped yet because the available technology is more expensive than the other clonal reproduction methods. The success of cocoa cuttings is influenced by genetic and environmental factors. The purpose of this research is to study effect of endogenous auxin content, effects of light intensity and exogenous auxin application, on the rooted cuttings. The 2 nd research purpose is to study effects of PVP (Polyvinylpyrrolidon) and IBA (β-indole-butyric acid), clones, and microclimate. The experiment was conducted in Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute in Jember (45 m a.s.l. and D rainfall type according to Schmidt Ferguson). The design for the 1 st experiment was splitsplit plot, replicated three times. The main plot was light intensity inside the roof, i.e.15%, 30%, and 45% to direct sun radiation. The sub plot was cocoa clones, i.e. DR 2 and ICS 13, and the sub-sub plot was IBA concentration, i.e. 0 ppm, 1500 ppm, 3000 ppm and 4500 ppm. The 2 nd experiment was designed factorial 3 x 3 of CRD, replicated 3 times. Clones of KW 163, KW 162 and KW 165, and IBA at 0, 3000, and 6000 ppm were the factors. In the same time, effect of IBA 6000 ppm, PVP 6000 ppm IBA+PVP 6000 ppm, and control were observed using KW 165 clone, and designed in complete randomized design (CRD), replicated 3 times. The result showed that auxin content of ICS 13 was higher than DR 2 (62.67 ppm vs 40.90 ppm) so that gave higher rooted cuttings and more root number. Exogenous application of IBA improved auxin content of the cutting materials and promoted root growth. The optimum IBA concentration for root number was 3500 ppm. Light intensity of 45% improved number of rooted cuttings three times compared to 15%, however compared to the 2 nd research, percentage of rooted cuttings was still very low. Cocoa cutting method to gain rooted cuttings 80—90% has been obtained. The method was using IBA 3000 ppm or 6000 ppm mixtured with or without PVP 6000 ppm, conducted during rainy season, the nursery using permanent shade trees of leucena sp., temperature of 24—27oC and relative humidity was 78—87%. PVP was supposed inhibit oxidation of IBA so that the effect of IBA was more optimum. The response of KW 162, KW 163 and KW 165 clones to root were similar. Rooted cuttings during dry season was low due to the less fresh of cutting materials and high temperature inside the bed roof. Key Words: Theobroma cacao, cuttings, light intensity, auxin, β-indole-butyric acid, Polyvinylpyrrolidon